Foreign Tutor-Based English Learning and Its Impact on Students’ Learning Interest in Pesantren - Kanafi, Lusi Nur; Faruk, Ahmad (Makassar State University, 2026)
This study analyzes the impact of foreign tutor-based English language learning on improving students' interest in learning at Pondok Pesantren Al-Munawwiri Sempu Islamic. The purpose of this study is to examine the role of foreign tutors in shaping, fostering, and maintaining students' interest in learning in the context of Islamic Pesantren education, which has distinctive social, cultural, and religious characteristics. This study uses a qualitative approach with a descriptive case study design. Research data were collected through learning observations, semi-structured interviews with five students, two teachers, the advisor, and foreign tutors, and supported by an analysis of relevant learning documents. The data were analyzed thematically to identify patterns and dynamics in the development of students' interest in learning. The results show that foreign-tutor-based English learning has a significant impact on the continuous improvement of students' interest in learning. Learning interest develops from a situational response to a more stable interest, reflected in increased curiosity, courage to ask questions, active participation, and students' confidence in using English. The implications of this research show that foreign tutors can be effective triggers if supported by pedagogical approaches that are in line with Pesantren culture